Understanding the Effects of Social Media Marketing Activities: Mediation of Social Identification, Perceived Value and Satisfaction - Ana Ana; Unggul Kustiawan (Jurnal Syntax Admiration, 2025)
Social media's role has grown significantly, emerging as a powerful tool for companies to execute marketing strategies. While numerous studies have delved into social media, few have delved into the impact of Social Media Marketing Activities. This research examines the effects of such activities on Social Identification, Perceived Value, and Satisfaction. To empirically assess these effects, an online survey was conducted among 350 social media users for data analysis. The findings reveal that Social Media Marketing Activities indirectly influence Satisfaction through Social Identification and Perceived Value. Additionally, Social Identification and Perceived Value have a direct impact on Satisfaction, subsequently affecting Continuance Intention, Participate Intention, Purchase Intention, and Revisit Intention. This study offers managerial insights for companies in the marketing realm, emphasizing the importance of crafting and implementing innovative marketing strategies on social media that align with consumer preferences. This, in turn, fosters Social Identification and cultivates positive consumer perceived value, ultimately leading to enhanced Satisfaction.